The Ethics of Risk: Ethical Analysis in an Uncertain World - Hansson, Sven Ove (Palgrave Macmillan, 2013)
When is it morally acceptable to expose others to risk? Most moral philosophers have had very little to say in answer to that question, but here is a moral philosopher who puts it at the centre of his investigations